Gas Exchange, Water Relations and their Relationships with Photochemical Reflectance Index in Quercus ilex Plants during Water Stress and Recovery - Tsonev, Tsonko; Wahbi, Said; Sun, Pengsen; Sorrentino, Giuseppe; Centritto, Mauro (INTERNATIONAL JOURNAL OF AGRICULTURE AND BIOLOGY, 2014)
Diffusional limitations to photosynthesis (A), relative water content (RWC) and their association with photochemical reflectance index (PRI) were studied in holm oak (Quercus ilex L.) saplings subjected to water stress and subsequent water stress relief. RWC decreased sharply as drought progressed. Following rewatering, RWC gradually increased to pre-stress values. A, stomatal conductance (g(s)), mesophyll conductance (g(m)), total conductance (g(t)), and PRI changed in parallel with RWC. A decrease in A resulted from coordinated suppression in leaf conductance. As water stress progressed, A measured in non-photorespiratory conditions (A(1%O2)) became more than 3 times higher compared to that recorded at 21% \{[\}O-2], indicating that photorespiration likely increased in response to water stress. A(1%O2) was significantly correlated with all leaf conductances. A(1%O2) was limited more by g(s) than by g(m), indicating that higher g(m) favors photosynthesis over photorespiration. There was a significant linear correlation between RWC and PRI. Significant non-linear relationships were also found both between PRI and A and PRI and g(t). These data imply that PRI may clearly detect normal and stressed status of holm oak, but it is not very informative when plants are severely stressed. Overall, our data indicate that: a) PRI is an important indicator of leaf water status as evident from RWC; b) because leaf conductance did not limit photosynthesis when photorespiration was suppressed, holm oak, and in general sclerophyllous species, will respond to future elevated \{[\}CO2] significantly more than mesophyllous plants; c) PRI can be used to predict changes in the performance of holm oak subjected to physiological water stress, whereas caution is needed under severe drought. (C) 2014 Friends Science Publishers
The following values have no corresponding Zotero field: pub-location: 399-B, PEOPLES COLONY NO 1, FAISALABAD, 38090, PAKISTAN publisher: FRIENDS SCIENCE PUBL
Keywords: CO2 transport conductance; Drought; leaf gas exchange; photorespiration; Relative water content; Spectral reflectance index